2010
DOI: 10.1016/j.carpath.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes in fibrillar collagen in myxomatous mitral valve disease

Abstract: Mild to moderate MMVD in the dog is associated with a marginal decline in collagen content in overtly diseased areas of valves, but more importantly is associated with an increase in immature collagen content. These changes will contribute to the mechanical dysfunction of the leaflet, and this study provides important information on the structure-mechanical alterations associated with this disease. The data suggests MMVD involves a dyscollagenesis process in the development of valve pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…In our samples, the denaturation endotherm was followed by an equilibrium state adequate to the new configuration of the protein molecules at temperatures just above 70°C. Similar values of denaturation temperatures are reported for samples from other collagenbased tissues [8,10,22,23]. Thermal stability of collagen molecules reflects the overall condition of the structure, cross-links in the collagen network, and its interactions with the surrounding molecules [4,21,[24][25][26].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our samples, the denaturation endotherm was followed by an equilibrium state adequate to the new configuration of the protein molecules at temperatures just above 70°C. Similar values of denaturation temperatures are reported for samples from other collagenbased tissues [8,10,22,23]. Thermal stability of collagen molecules reflects the overall condition of the structure, cross-links in the collagen network, and its interactions with the surrounding molecules [4,21,[24][25][26].…”
Section: Discussionsupporting
confidence: 73%
“…The DSC method has proven to be a valuable tool in assessing the role of collagen in structural alterations of several cardiovascular and musculoskeletal diseases [8][9][10][11]. Our previous study showed that DSC was the appropriate method for investigation of subtle changes in physicochemical conditions of peritoneum using tissues obtained during surgical procedures [12].…”
Section: Introductionmentioning
confidence: 99%
“…DSC studies have proved to be valuable in assessing the role of collagen in structural alterations of aortic walls in abdominal aortic aneurysms and in mechanical alterations associated with mitral valve dysfunctions, as well as in the characterization of aortic tissues for cardiac valve bioprostheses and artificial blood vessels [16][17][18][19]. The calorimetric method has been successfully applied in investigations of collagen in mineralized bone tissue [11,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there is not a panel of diagnostic and prognostic biomarkers for sporadic forms, and their physiopathology remains unclear. Echocardiography evaluation represents until now unique "gold standard diagnostic" tool, even if it always reveals no appropriate for diagnosing moderate forms [3][4][5]. This underlines the necessity of innovative biomarker tools to identify in molecular pathways associated with mechanisms related to MVD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This underlines the necessity of innovative biomarker tools to identify in molecular pathways associated with mechanisms related to MVD pathogenesis. Recently, it is emerging that degenerative MVDs are the result of modified adult valve biology [4,5]. Particularly, Levine and colleagues have recently underlined that MVDs are the result of a 'living valve', which with advancing age shows active changes mediated both by valvular endothelial and interstitial cells and alterations in composition and turnover of elements of extracellular matrix [6].…”
Section: Introductionmentioning
confidence: 99%